2014
DOI: 10.1111/1756-185x.12380
|View full text |Cite
|
Sign up to set email alerts
|

High serum level of haptoglobin is associated with the response of 12 weeks methotrexate therapy in recent‐onset rheumatoid arthritis patients

Abstract: Background: We previously found, using microarray, haptoglobin (HP) expression signal was 5.1-fold increased in peripheral blood mononuclear cells (PBMCs) from methotrexate (MTX)-resistant rheumatoid arthritis (RA) patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
(40 reference statements)
2
4
0
Order By: Relevance
“…1). The results were similar to studies that demonstrated that HP is an important activator of immune cells (16)(17)(18). Based on these results, we conjectured that HP plays important roles in B-cell activation.…”
Section: Discussionsupporting
confidence: 89%
“…1). The results were similar to studies that demonstrated that HP is an important activator of immune cells (16)(17)(18). Based on these results, we conjectured that HP plays important roles in B-cell activation.…”
Section: Discussionsupporting
confidence: 89%
“…As a result, the mRNA level of haptoglobin in CIKs treated with gentamicin was significantly downregulated by 1.73-fold compared with the control group. This is similar to the finding that haptoglobin expression signal was decreased 5.1-fold in peripheral blood mononuclear cells from healthy participants compared with methotrexate-resistant patients with rheumatoid arthritis (38). Herein, these results suggest that haptoglobin was involved in the activity-enhancement of CIKs.…”
Section: Discussionsupporting
confidence: 88%
“…A similar association with serum TNF-α was found by another research group 21 . In a Chinese study of patients with eRA, it was shown that high serum levels of haptoglobin were associated with response to MTX therapy 22 . A study of treatment-naive eRA patients in India demonstrated that serum baseline levels of myeloid-related protein 8/14 were significantly higher in responders versus nonresponders to 4 months of MTX monotherapy, according to European League Against Rheumatism (EULAR) criteria 23 .…”
mentioning
confidence: 99%